Delayed-onset recurrent spinal epidural hematoma: A case of unusual postoperative complications in a high-risk patient - Guive Sharifi; Elham Paraandavaji; Mohammad Mehdi Mousavi Nasab; Bardia Hajikarimloo; Esmaeil Mohammadi; Mehdi Pourghazi (Interdisciplinary Neurosurgery)
Background: Recurrent postoperative spinal epidural hematoma (PSEH) following spinal surgery is an exceedingly rare condition, primarily affecting the lower cervical and upper thoracic regions. Delayed-onset PSEH, which occurs between three days and two weeks after surgery, poses distinct diagnostic and therapeutic challenges. Case presentation: A patient in his 70 s, with multiple comorbidities including type 2 diabetes and chronic kidney disease, underwent a C1-C5 posterior neck laminectomy and fusion to address C1-C2 instability and significant canal stenosis. Ten days after the procedure, he developed right-sided hemiplegia, prompting an MRI that revealed spinal epidural hematoma. Remarkably, ten days following a second surgery to evacuate the hematoma, the patient experienced another recurrence, requiring yet another evacuation. Fortunately, he recovered fully without any lasting neurological deficits. Conclusion: Recurrent delayed-onset PSEH, while rare, can lead to severe consequences if not diagnosed and treated accordingly. Increased awareness and early intervention are essential to mitigate the risk of permanent neurological impairment, particularly in high-risk patients.